The temporal fossa and temporomandibular joint (TMJ) - Dias, George (Henry Stewart Talks, 2024)
Temporal fossa, Temporomandibular joint (TMJ), Joint capsule and synovial membrane, Ligaments in the TMJ, Movements at the TMJ, Blood and sensory nerve supply to the TMJ